A mediation model linking attachment to God, self-compassion, and mental health - Homan, Kristin J. (Mental health, religion & culture, 2014)
Attachment theory posits that insecure attachment is a risk factor for the development of anxiety and depression and ample evidence supports this idea. Research has also demonstrated links between attachment to God and mental health, but little is known about the emotion regulatory mechanism that underlies this relationship. The present study explored the explanatory role of self-compassion in the relation between attachment to God and anxiety, depression, and life satisfaction in a sample of 181 adults who completed an online survey. Elevated attachment anxiety and avoidance were associated with higher depression and anxiety, and lower life satisfaction. Self-compassion mediated these associations (in an inverse direction for anxiety and depression), suggesting that people who feel uncomfortable depending on God, or who fear God's rejection, have difficulty extending kindness to themselves. Possible interventions are discussed in the context of these results.